CD40 Activity on Mesenchymal Cells Negatively Regulates OX40L to Maintain Bone Marrow Immune Homeostasis Under Stress Conditions - Bassani, Barbara; Tripodo, Claudio; Portararo, Paola; Gulino, Alessandro; Botti, Laura; Chiodoni, Claudia; Jachetti, Elena; Bolli, Niccolò; Ciciarello, Marilena; Joehrens, Korinna; Anagnostopoulos, Ioannis; Na, Il-Kang; et al. (Frontiers in Immunology, 2021)
Background Within the bone marrow (BM), mature T cells are maintained under homeostatic conditions to facilitate proper hematopoietic development. This homeostasis depends upon a peculiar elevated frequency of regulatory T cells (Tregs) and immune regulatory activities from BM-mesenchymal stem cells (BM-MSCs). In response to BM transplantation (BMT), the conditioning regimen exposes the BM to a dramatic induction of inflammatory cytokines and causes an unbalanced T-effector (Teff) and Treg ratio. This imbalance negatively impacts hematopoiesis, particularly in regard to B-cell lymphopoiesis that requires an intact cross-talk between BM-MSCs and Tregs. The mechanisms underlying the ability of BM-MSCs to restore Treg homeostasis and proper B-cell development are currently unknown. Methods We studied the role of host radio-resistant cell-derived CD40 in restoring Teff/Treg homeostasis and proper B-cell development in a murine model of BMT. We characterized the host cellular source of CD40 and performed radiation chimera analyses by transplanting WT or Cd40-KO with WT BM in the presence of T-reg and co-infusing WT or - Cd40-KO BM-MSCs. Residual host and donor T cell expansion and activation (cytokine production) and also the expression of Treg fitness markers and conversion to Th17 were analyzed. The presence of Cd40+ BM-MSCs was analyzed in a human setting in correlation with the frequency of B-cell precursors in patients who underwent HSCT and variably developed acute graft-versus-host (aGVDH) disease. Results CD40 expression is nearly undetectable in the BM, yet a Cd40-KO recipient of WT donor chimera exhibited impaired B-cell lymphopoiesis and Treg development. Lethal irradiation promotes CD40 and OX40L expression in radio-resistant BM-MSCs through the induction of pro-inflammatory cytokines. OX40L favors Teff expansion and activation at the expense of Tregs; however, the expression of CD40 dampens OX40L expression and restores Treg homeostasis, thus facilitating proper B-cell development. Indeed, in contrast to dendritic cells in secondary lymphoid organs that require CD40 triggers to express OX40L, BM-MSCs require CD40 to inhibit OX40L expression. Conclusions CD40+ BM-MSCs are immune regulatory elements within BM. Loss of CD40 results in uncontrolled T cell activation due to a reduced number of Tregs, and B-cell development is consequently impaired. GVHD provides an example of how a loss of CD40+ BM-MSCs and a reduction in B-cell precursors may occur in a human setting.